Extracellular acidosis differentiates pancreatitis and pancreatic cancer in mouse models using acidoCEST MRI - Rachel A. High; Edward A. Randtke; Kyle M. Jones; Leila R. Lindeman; Jacqueline C. Ma; Shu Zhang; Lucia G. LeRoux; Mark D. Pagel (Neoplasia: An International Journal for Oncology Research, 2019)
Differentiating pancreatitis from pancreatic cancer would improve diagnostic specificity, and prognosticating pancreatitis that progresses to pancreatic cancer would also improve diagnoses of pancreas pathology. The high glycolytic metabolism of pancreatic cancer can cause tumor acidosis, and different levels of pancreatitis may also have different levels of acidosis, so that extracellular acidosis may be a diagnostic biomarker for these pathologies. AcidoCEST MRI can noninvasively measure extracellular pH (pHe) in the pancreas and pancreatic tissue. We used acidoCEST MRI to measure pHe in a KC model treated with caerulein, which causes pancreatitis followed by development of pancreatic cancer. We also evaluated the KC model treated with PBS, and wild-type mice treated with caerulein or PBS as controls. The caerulein-treated KC cohort had lower pHe of 6.85–6.92 before and during the first 48 h after initiating treatment, relative to a pHe of 6.92 to 7.05 pHe units for the other cohorts. The pHe of the caerulein-treated KC cohort decreased to 6.79 units at 5 weeks when pancreatic tumors were detected with anatomical MRI, and sustained a pHe of 6.75 units at the 8-week time point. Histopathology was used to evaluate and validate the presence of tumors and inflammation in each cohort. These results showed that acidoCEST MRI can differentiate pancreatic cancer from pancreatitis in this mouse model, but does not appear to differentiate pancreatitis that progresses to pancreatic cancer vs. pancreatitis that does not progress to cancer.